2017
DOI: 10.1016/j.tics.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Memory Reconsolidation Updating

Abstract: The reactivation of a synaptically stored memory in the brain can make the memory transiently labile. During the time it takes for the memory to re-stabilize (reconsolidate), the memory can either be reduced by an amnesic agent or enhanced by memory enhancers. The change in memory expression is related to changes in the brain correlates of long-term memory. Many have suggested that such retrieval-induced plasticity is ideally placed to enable memories to be updated with new information. This hypothesis has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
368
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(408 citation statements)
references
References 139 publications
11
368
1
5
Order By: Relevance
“…In a familiar context, the organism can bring its past experience in the context to bear on upcoming decisions and actions. Violations of predictions formed from past experiences in the context could lead to the formation of an entirely new context representation, or alternatively, the new information could be accommodated within an already existing context map—these phenomena are currently being studied under the rubric of ‘memory reconsolidation’ 14 , ‘memory updating’ 1518 , and ‘integrative encoding’ 19 . In other words, hippocampal context representations can stimulate exploratory behavior, inform decisions from past experience, or rapidly update our understanding of the current state of the world.…”
Section: What Is the Global Function Of The Hippocampus And How Doesmentioning
confidence: 99%
“…In a familiar context, the organism can bring its past experience in the context to bear on upcoming decisions and actions. Violations of predictions formed from past experiences in the context could lead to the formation of an entirely new context representation, or alternatively, the new information could be accommodated within an already existing context map—these phenomena are currently being studied under the rubric of ‘memory reconsolidation’ 14 , ‘memory updating’ 1518 , and ‘integrative encoding’ 19 . In other words, hippocampal context representations can stimulate exploratory behavior, inform decisions from past experience, or rapidly update our understanding of the current state of the world.…”
Section: What Is the Global Function Of The Hippocampus And How Doesmentioning
confidence: 99%
“…Following exposure to a stimulus that reactivates this circuit, the memory trace becomes labile again, allowing it to be manipulated pharmacologically. Reconsolidation has been proposed as a potential strategy to erase unwanted memories in conditions associated with adverse events, such as in post-traumatic stress disorder (PTSD) [75,76]. Remarkably, reconsolidation also occurs in the spinal cord [74,77,78], raising the potential for therapeutic strategies based on this approach.…”
Section: Targeting Translation For Therapeutic Development Of Next-gementioning
confidence: 99%
“…In the second phase, mice underwent place counterconditioning with water-flood, 45 min after memory retrieval by a brief re-exposure to the alcohol-paired compartment (Retrieval group) or handling (control, No Retrieval group). The 45-min interval was chosen for the counterconditioning to be held within the 'reconsolidation window' (Nader and Hardt, 2009;Xue et al, 2012;Lee et al, 2017). The subsequent Place preference test 2 confirmed that aversive counterconditioning led to the loss of place preference in both groups ( Figure 1B).…”
Section: Resultsmentioning
confidence: 76%
“…Current concepts suggest that memories undergo de-stabilization upon their reactivation via memory retrieval, and then restabilize within a few hours in a process termed "reconsolidation" (Przybyslawski and Sara, 1997;Nader et al, 2000). While in a temporary active state (termed "reconsolidation window"), memories can be disrupted, updated, or strengthened (Nader and Hardt, 2009;Nader, 2015;Dunbar and Taylor, 2017b;Lee et al, 2017;Gisquet-Verrier and Riccio, 2018), providing a promising therapeutic approach for relapse prevention in addiction (Tronson and Taylor, 2013;Vousden and Milton, 2017;Exton-McGuinness and Milton, 2018). It is established that memory reconsolidation can be disrupted by pharmacological manipulations (Nader et al, 2000;Dunbar and Taylor, 2017b).…”
Section: Introductionmentioning
confidence: 99%